Role of the mitochondrial regulatory factor CHCHD2 in neurodegenerative diseases - Guo, Xinyu; Xu, Peiyu; Liang, Chen; Li, Yuntao (Frontiers in Neuroscience, 2025)
Mitochondria are essential organelles within cells, and their dysfunction is associated with many neurodegenerative disorders. The protein CHCHD2, which is situated in the intermembrane space of mitochondria, plays a pivotal role in mitochondrial function. Its knockdown or mutation is linked to mitochondrial impairment. Although research suggests that CHCHD2 is involved in the mechanisms underlying various neurodegenerative diseases, there is a notable absence of comprehensive studies that integrate different mutation types, pathogenic mechanisms, and targeted treatment strategies. This paper provides a review of CHCHD2’s structure and function, mutant varieties, biological models, and relevant therapies. We conclude that CHCHD2 is critical for maintaining mitochondrial homeostasis, facilitating cell migration, and regulating apoptosis. Mutations in CHCHD2 may influence the mechanisms of neurodegenerative diseases through both loss-of-function and gain-of-function effects, with overexpression possibly reversing pathological processes and mitochondrial dysfunction. Furthermore, elamipretide, a novel drug that targets mitochondria, has shown efficacy in partially alleviating mitochondrial defects resulting from CHCHD2 mutations. These insights could inform the identification of therapeutic targets in neurodegenerative diseases and shape future research on CHCHD2.